AN EXPLORATION OF ANGER EXPRESSION IN INDONESIAN EFL LEARNING CONTEXT - Susiati, Susiati (Universitas Muhammadiyah Surakarta, 2016)
This study investigates how the students of the Department of English Education, Universitas Muhammadiyah Surakarta express their anger in English as anger is an expression which relies on contexts. The studentsâ conversations which contained anger expression were recorded. The expressions were analyzed based on pragmatic aspects: pragmalinguistic forms, communicative intention, context, and cultural background. The results showed that the students, mostly Javanese, did not use cursing or swearing forms in expressing anger in English which are typically in âdirect angerâ and âintroductory angerâ. Interestingly, although Javanese people arewell-known as calm people, the students mostly rise their intonation in expressing their anger feeling in English.